PSYCHOLOGICAL MEANS OF OVERCOMING MONOTONOUS INFLUENCES DURING PERFORMANCE - Halajyan , W. M. (Modern Psychology, 2019)
Real changes in the conditions of professional activity of civil servants impose special requirements on the maintenance of an adequate state for the performance of work. The purpose of the study was to reveal the psychological aspects of preventive methods with monotonic effects during professional performance. In the process of the study, musical pauses were specially selected that would allow to overcome the monotonous influences in the professional activity of civil servants during the working day.